UPPER AIRWAY SLEEP DISORDERS AND DENTAL TREATMENT - Baskar, Sharwini; S, Kavitha.; S, Preetha.; V. , Vishnupriya; R, Gayathri (International Journal of Psychosocial Rehabilitation, 2020)
In recent year's, about 3% of the middle-aged population suffers from daytime sleepiness and nighttime sleep interruptions; it may be due to upper airway sleep disorders (UASD). A UASD is the narrowing of the upper airway and results in disruptions of sleep, affects health and lifestyle, and less concentration in work. Most of the automobile and work accidents are due to sleeplessness. It can also cause critical medical conditions. Apnea is the complete cessation of breath, and hypopnea is a reduction in the airflow. Obstructive sleep apnea (OSA) affects 4% of males and 2% of females. In a normal person, airway space is free for air passage, and in a disordered person, the airway space is compromised, which makes it difficult for the passage of air. There are multifactorial factors that can cause UASD. They are the position of muscles and anatomical alterations. In supine, the muscles tensor veli palatini and genioglossus have decreased activity. Anatomical alterations such as posteriorly positioned maxilla and mandible, overerupted anterior teeth, large gonial angle, and long tongue may reduce the upper airway space. There are various treatments for UASD. Dental treatment options such as a tongue retaining device (TRD) and a mandibular advancement device. This study reviewed the dental treatment involved in the treatment of UASD, the surgical methods involved, and also the failure of dental treatment. Many snoring and OSA patients were successfully treated using dental devices. UASD is treated successfully using oral devices. Dental treatments are successful in treating mild to moderate OSA.